ANALYSIS AND SYSTEMATIZATION OF VARIETIES OF DESIGN SOLUTIONS IN THE MANUFACTURE OF ADAPTIVE CLOTHES FOR PATIENTS - Колосніченко, О. В.; Пашкевич, К. Л.; Остапенко, Н. В.; Люклян, Н. Р.; Скріпченко, А. Г. (Art and Design, 2023)
Purpose: to analyze and systematize the types of design solutions of individual elements and components in the manufacture of adaptive clothing for patients. Methodology. The system approach, methods of retrospective, theoretical and system-structural analysis are applied. Results. The list of the leading world and domestic companies of manufacturers is presented and the range of the existing adaptive shoulder and waist clothes is investigated. The constructive-technological solutions of adaptive clothing for patients are singled out and systematized according to such features as silhouette, sleeve cut, design of upper and lower sections, functional-constructive and constructive-decorative elements, type of fasteners. Rational constructive and technological solutions of shoulder and waist products for patients in accordance with the requirements for them are proposed. Scientific novelty. On the basis of theoretical researches of the existing kinds of adaptive products the information base of constituent elements of shoulder and waist products for patients for the purpose of their reasonable choice is formed. The most rational constructive-technological decisions of constituent elements of products are systematized. The practical significance. Based on the study and analysis of world analogues of clothing for patients, new design and technological solutions with improved performance and ergonomics.